Possible involvement of vitamin K insufficiency in the progression of cervical ossification of the posterior longitudinal ligament - Atsushi Kimura; Naoya Taki; Yukinori Hayashi; Yasuyuki Shiraishi; Tsukasa Ohmori; Katsushi Takeshita (Scientific Reports)
Abstract Ossification of the posterior longitudinal ligament of the vertebral column (OPLL) is a disease characterised by ectopic bone formation in the spinal ligament that causes progressive neurological impairment. However, there are no suitable treatments for OPLL. Here, we compared the general characteristics and haemostasis of patients with OPLL and those with cervical spondylotic myelopathy. Those with OPLL had significantly longer prothrombin times and lower plasma protein C concentrations, consistent with vitamin K deficiency. Therefore, we next characterised the effects of vitamin K supplementation on spinal hyperostosis in ttw mice, a model of cervical OPLL, by feeding them standard chow, vitamin K-deficient chow, or standard chow accompanied by biweekly vitamin K2 injections for 6 weeks. We found that vitamin K supplementation resulted in longer stride lengths and superior inter-limb coordination using footprint analysis. Furthermore, supplementation caused a significant reduction in ectopic calcification of the cervical ligaments of the mice, according to microcomputed tomography analysis. Finally, supplementation caused an increase in the number of osteochondrogenic cells expressing Gla-rich protein, an inhibitor of ectopic calcification, and increased the circulating concentration. Thus, vitamin K insufficiency may be involved in the pathogenesis of OPLL and supplementation may represent a novel treatment for this condition.